Strategi Harga Dan Kualitas Pelayanan Pada Penjual Bakso Terhadap Kepuasan Pelanggan (UMKM Bakso Pakde Universitas Bhayangkara) - Dian Sudiantini; Faidlullah Mahfudz; Muhammad Zaky; Rizka Amalia Putri; Sunia Hatina (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
In Indonesia, small and medium-sized businesses (SMBs) in the food and drink industry are seeing unprecedented expansion. Lots of MSMEs are experiencing this as they try to win over consumers. With competition heating up in the food stall industry, the research focuses heavily on what makes customers happy. A food stand may increase customer satisfaction by focusing on three areas: price, service, and product quality. Setting reasonable prices, giving outstanding service, and delivering high-quality goods are all ways to make customers happy at the food stand. Satisfied customers will be more likely to return to the store. The sales income of Bakso Pakde has recently seen significant adjustments. Finding out how different pricing tactics, product modifications, and service quality affect "Bakso Pakde" consumer happiness is the main goal of this research. This research makes use of SPSS for statistical analysis, which is part of a quantitative technique. "Bakso Pakde" customers are the center of attention in this research. For this study, 42 participants were chosen at random using a purposive selection technique. Multiple linear regression is the method that the analytical tool uses. This research found that in the setting of meatball vendors, consumer happiness was positively affected by price, product selection, and service quality.